RELACIJE MORFOLOŠKIH KARAKTERISTIKA I TESTOVA ZA PROCJENU EKSPLOZIVNE SNAGE KOD MLADIH RUKOMETAŠA - Miroslav Živković; Slobodan Goranović; Saša Marković; Nataša Branković (University of Banja Luka, Faculty of physical education and sport, 2010)
The authors have carried out this research on a sample of 50 young handball students,beginners at the school of handball in Ni{, aged 11 and 12. The aim of the research was todetermine the canonical relations of morphological characteristics on the one hand, and tests forthe evaluation of explosive strength on the other, among young handball players. The subjectmatter of the research was to study the extent of the influence of morphological characteristics onthe achieved results of explosive strength. Ten anthropometric measures for morphologicalcharacteristics which define the longitudinal and transversal dimensionality of the skeleton andcircular dimensionality and body mass. Explosive strength was evaluated by means of three tests.The results of the correlation analysis have shown that a significant canonical factor as well as ahigh correlation exist between morphological dimensions (as the predictor system) and explosivestrength (as criterion system).young handball players, morphological characteristics, explosive strength.